Women in the Malestream Study of Crime: Exploring Three Swedish Journals throughout the Last Century - Camenius, Robin (Women & criminal justice, 2023)
The present article seeks to add further empirical nuance and specification to ongoing debates on the androcentric biases of historical and present research on crime. Using a mixed-methods design, it examines gender differences in theorizing and how women are represented in Swedish crime-related research between 1920 and 2015. On the one hand, the quantitative analysis reveals that explanations and proposed solutions to crime are more gender-neutral than previous research tends to suggest. On the other hand, the qualitative analysis uncovers how women are rendered visible almost exclusively in discussions on crime that concern issues linked to the body, sex and sexuality, or victimhood and vulnerability. Generally, in the Swedish context, characterized by the establishment of a strong welfare state, women and women’s criminality have primarily been given relevance in the context of larger socio-economic problems and/or reforms.